2010
DOI: 10.1002/arch.20370
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a prolyl endoprotease from Eurygaster integriceps puton (Sunn pest) infested wheat

Abstract: Sunn pest, Eurygaster integriceps, Puton, infested and uninfested wheat seeds were obtained from the International Center for Agriculture Research in the Dry Areas (ICARDA), Aleppo, Syria, with the primary objective to identify the type of enzyme deposited by the Sunn pest on the wheat responsible for the gluten degradation. Enzyme levels were extremely low due to the enzyme being secreted by the insect in localized areas on the seed. Only extract from the infested wheat contained glutenase activity. Anion exc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 33 publications
(31 reference statements)
2
24
0
2
Order By: Relevance
“…This finding is consistent with previous study of Darkoh et al (2010) using phenylmethylsulphonyl floride (PMSF) as a commercial protease inhibitor for Eurygaster protease(s). The effect of EDTA-Na 2 confirmed that metal ions were essential to action or stability of the bug enzyme(s).…”
Section: Effects Of Commercial Protease Inhibitorssupporting
confidence: 94%
See 1 more Smart Citation
“…This finding is consistent with previous study of Darkoh et al (2010) using phenylmethylsulphonyl floride (PMSF) as a commercial protease inhibitor for Eurygaster protease(s). The effect of EDTA-Na 2 confirmed that metal ions were essential to action or stability of the bug enzyme(s).…”
Section: Effects Of Commercial Protease Inhibitorssupporting
confidence: 94%
“…The major role of them is plant protection by blocking the digestive proteolytic enzymes of invading pests (Gatehouse, 1984). It was reported that a phenylmethylsulphonyl floride (PMSF), a commercial serine protease inhibitor, was inhibited Eurygaster and Nysius proteases (Darkoh et al, 2010;Every, 1993). The protease from Nysius huttoni was insensitive to most proteinaceous inhibitors except for potato inhibitor I and some divalent metal ions such as Co 2þ , Mn 2þ , Fe 2þ (Cressey, 1987;Every, 1993).…”
Section: Introductionmentioning
confidence: 98%
“…The PEP from E. integriceps (cf. above) was also tested for its ability to degrade gluten (Darkoh et al 2010). The enzyme activity was shown by use of an SDS-gluten assay, in which hydrolytic activity led to a degradation of the glutencontaining gel.…”
Section: Degradation Of Glutenmentioning
confidence: 99%
“…They detected 31 digestive enzymes, whereof four enzymes were identified as serine peptidases. Darkoh et al (2010) characterised a PEP from E. integriceps. In this study, the enzyme was not isolated from the beetle itself, but from infested wheat grains.…”
Section: Insectsmentioning
confidence: 99%
“…In recent years great progress has been made in the study of interaction mechanisms of bugs with plant seeds (Hosseininaveh et al, 2009;Darkoh et al, 2010;Mehrabadi et al, 2010;Zibaee et al, 2011).…”
Section: Introductionmentioning
confidence: 99%